Crack initiation and propagation on the polymeric material ABS (Acrylonitrile Butadiene Styrene), under ultrasonic fatigue testing (Fracture and Structural Integrity, 2015)
Crack initiation and propagation have been investigated on the polymeric material ABS (Acrylonitrile Butadiene Styrene), under ultrasonic fatigue testing. Three controlled actions were implemented in order to carry out fatigue tests at very high frequency on this material of low thermal conductivity, they are: a) The applying load was low to limit heat dissipation at the specimen neck section, b) The dimensions of testing specimen were small (but fitting the resonance condition), in order to restraint the temperature gradient at the specimen narrow section, c) Temperature at the specimen neck section was restrained by immersion in water or oil during ultrasonic fatigue testing. Experimental results are discussed on the basis of thermo-mechanical behaviour: the tail phenomenon at the initial stage of fatigue, initial shear yielding deformation, crazed development on the later stage, plastic strain on the fracture surface and the transition from low to high crack growth rate. In addition, a numerical analysis is developed to evaluate the J integral of energy dissipation and the stress intensity factor K, with the crack length
Keywords: Polymeric material